A listener in a musical work - Moskalenko, Victor (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. The development of musical culture takes place in the commonwealth of creative processes of the composer, musician-performer and listener. At the same time, to the last of the listed categories is not given enough attention in modern musicology. This especially applies to music-theoretical explorations of the music listener’s participation in the formation of the semantic space of a musical work. The focus is on the category of the mass (average) listener, the vast majority of whom do not know much about music. The purpose of the article is to consider the function of the average music listener in the integral communicative structure of a musical work, which is expressed by the sequence: composer — performer — listener. The methodology. The theoretical position proposed in the article is based on the key points of the concept of musical interpretation by V. G. Moskalenko. It is about the understanding of intonation, the music-intonation triad, in which the movement of musical thinking from the intonation model to the intonation-result is symbolically presented, as well as three types of the text of a musical work. To analyze the creative function of the listener in the semantic field of a musical work, a musical-genetic approach is used, which is indicative of the movement of musical thought from its ancestral foundations to the final result. In this aspect, the following are developing: A) M. Mykhaylov’s theoretical approach regarding intonation bases of creative activity of musical thinking; B) terminological differentiation of the principle of musical intonation in relation to the composer, musician-performer and listener. Results and conclusions. The formation of the semantic space of a musical work is considered in the trinity of the creative action of the composer, musician-performer and listener. In the category of music listeners, two types are distinguished: professional and average (mass) listener. The focus is on the average listener. The research uses the musical-genetic method, which involves the sequential movement of musical or cognitive thought from the ancestral foundations through the stage of formation to the final result. Three groups of texts of a musical work are identified, which are informants about its artistic identity: sheet music, text-sound and psychological text. The role of the psychological text in the formation of the semantic field of a musical work is emphasized. In the development of M. Mykhaylov’s intonation concept of musical thinking, the effect of the three-link structure of the formation of the musical thought of the composer, the musician-performer, and the average listener is separately traced. The importance of the relatively independent function of the average listener in the social "biography" of the interpretive life of a musical work is emphasized, which ultimately affects the variant renewal and even the development of its semantic field. The conclusion is made about the need to support the development of the intonation-creative initiative of the average listener in any possible way conditions of modern forms.